KARAKTERISASI MATERIAL FEROELEKTROK Ba(1-x)Sr(x)TiO3 (BST) UNTUK KOMPOSISI x=0,1; 0,2 dan 0,3 - Rahmi Dewi; Krisman '; Zuhdi ' (Universitas Riau, 2015)
Barium Strontium Titanate, Ba0.9Sr0.1TiO3, Ba0.8Sr0.2TiO3 and Ba0.7Sr0.3TiO3 (BST) samples were prepared usingsolid state chemical reaction. The microstructure of these samples were characteritation using the X-ray Diffractiontechnique (XRD) and Scanning Electron Microscopy (SEM). Then the samples were composition variationdifferent annealed at 700oC a for 60 minutes in air. The XRD characterization showed that the crystallizationimproved as the barium increased. The microstructure showed that the samples were homogeny with the grainsize were uniform. The grain size samples increases with the strontium increased.